Differential effects of valley city morphology on mesoscale flow field characteristics. (November 2021) - Wu, Songheng; Chen, Canwen; Wang, Yi; Yu, Zhuolei; Cao, Jiaxuan; Zhang, Ruida; Song, Han
Abstract: The coupling of two mesoscale flows, slope wind and urban heat island circulation (UHIC), is the basic model of valley urban ventilation under calm and stable weather conditions. Under the influence of the economy, history, and landforms, cities may take different forms. However, the different effects of form transformation on the mesoscale flow field characteristics of valley cities under calm and stable weather have not been studied. In this paper, a numerical simulation method, called numerical water tank, is proposed to study the mesoscale flow by using the small-scale method, and then the differential effects of urban expansion and geometric shape transformation on the mesoscale flow field characteristics of valley cities are discussed respectively. This study elucidates the difference in the effects of the valley city form on the mesoscale flow field of valley cities under calm and stable weather conditions. From the perspective of the terrain effect and upslope wind effect, urban expansion is not conducive to the dissipation of heat and pollutants in urban areas. From the aspect of urban geometry, the conditions of atmospheric diffusion are most favorable in the two types of urban layouts: rectangle and square. Downslope wind plays a critical role in improving urban thermal and air environments. Highlights: The coupling effect of slope wind and urban UHIC is the basic model of valley city ventilation under static and stable weather. The influence of urban forms on mesoscale flow field of valley city has not been studied. Rectangular and square valley urban layout is the most favorable for atmospheric diffusion. Downslope wind plays an important role in improving the urban thermal and air environment.